# Solve for y (3y)/10-5=y/5+3

3y10-5=y5+3
Move all terms containing y to the left side of the equation.
Subtract y5 from both sides of the equation.
3y10-5-y5=3
To write -y5 as a fraction with a common denominator, multiply by 22.
3y10-y5⋅22-5=3
Write each expression with a common denominator of 10, by multiplying each by an appropriate factor of 1.
Multiply y5 and 22.
3y10-y⋅25⋅2-5=3
Multiply 5 by 2.
3y10-y⋅210-5=3
3y10-y⋅210-5=3
Combine the numerators over the common denominator.
3y-y⋅210-5=3
Simplify each term.
Simplify the numerator.
Factor y out of 3y-y⋅2.
Factor y out of 3y.
y⋅3-y⋅210-5=3
Factor y out of -y⋅2.
y⋅3+y(-1⋅2)10-5=3
Factor y out of y⋅3+y(-1⋅2).
y(3-1⋅2)10-5=3
y(3-1⋅2)10-5=3
Multiply -1 by 2.
y(3-2)10-5=3
Subtract 2 from 3.
y⋅110-5=3
y⋅110-5=3
Multiply y by 1.
y10-5=3
y10-5=3
y10-5=3
Move all terms not containing y to the right side of the equation.
Add 5 to both sides of the equation.
y10=3+5
y10=8
y10=8
Multiply both sides of the equation by 10.
10⋅y10=10⋅8
Simplify both sides of the equation.
Cancel the common factor of 10.
Cancel the common factor.
10⋅y10=10⋅8
Rewrite the expression.
y=10⋅8
y=10⋅8
Multiply 10 by 8.
y=80
y=80
Solve for y (3y)/10-5=y/5+3

## Our Professionals

### Lydia Fran

#### We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

Scroll to top